Enhancement or suppression: a double-edged sword? Differential association of digital literacy with subjective health of older adult-evidence from China - Qi-Song Yan; Qiao Guo (Frontiers Media S.A., 2024)
BackgroundThe emergence of an aging society and the digital age makes healthy aging a hot topic in Chinese society. This paper explores the associations between digital literacy and the subjective health of older adult individuals in PR China, offering insights that May assist policymakers and service providers in developing strategies and interventions suited to the digital era, potentially enhancing the healthy aging process for this demographic in China.MethodsThis study utilized data from the China Longitudinal Aging Social Survey. Initially, demographic variables of 2086 individuals in the sample were analyzed. Subjective health differences among different populations and correlations between core variables were examined. Subsequently, multivariate linear regression and chain mediation methods were utilized to examine the relationships and potential pathways among the three dimensions of digital literacy and the subjective health of older adult individuals.Results(1) The subjective health status of older adult individuals in China was generally favorable, with an average score of 3.406 ± 0.764. (2) There was no direct correlation observed between the frequency of digital information use and the subjective health of the older adult (b = −0.032, p > 0.1). Digital entertainment information (b = 0.294, p > 0.1) did not show a significant effect, whereas life management information (b = 0.437, p < 0.01) demonstrated a positive association. Similarly, the use of smart healthcare devices (b = 0.842, p < 0.001) indicated a positive association (3) The frequency of digital information use indirectly enhanced the subjective health of the older adult through life management digital information and the use of smart healthcare devices, but had no indirect effect through entertainment and leisure digital information.ConclusionDigital literacy is significantly correlated with the subjective health of the older adult, especially when they acquire life management information and utilize smart healthcare devices. However, a potential negative relationship is suggested between digital entertainment information and the subjective health of older adult individuals. Therefore, digital infrastructure should have prioritized the provision of high-quality, age-friendly digital applications for the older adult. This approach could have better harnessed the potential of digitalization to enhance health and well-being in older adults.